PENGARUH PLYOMETRIC UPPER BODY EXERCISE TERHADAP PENINGKATAN KEMAMPUAN SMASH ANGGOTA UKM BOLA VOLI UNIVERSITAS LAMPUNG - Prabowo, Dino; Candra Kurniawan; M.Fajril Rifaldo; Lungit Wicaksono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effect of plyometric upper body exercise on smash ability in members of the Volleyball Student Activity Unit (UKM) of the University of Lampung. The research method used was a comparative experiment. The sample used in this study was 30 members of the Volleyball Student Activity Unit (UKM) of the University of Lampung using the ordinal pairing technique. The instrument used was a smash ability test. The results of this study indicate that there is a significant effect of plyometric upper body exercise on smash ability in members of the Volleyball Student Activity Unit (UKM) of the University of Lampung. With the results of the t-test at a significant level of 5% (0.05), the calculated t-value was 13,775 > the t-table value = 2.131.